3D Printing Technology: A Contemporary Revolution in Drug Development (Asian Journal of Pharmaceutics (AJP), 2023)
As a recently developing technology, three-dimensional (3D) printing has a lot of potential in the pharmaceuticalsector and can cater patients and the pharmaceutical industry with innovative approaches. This technology allowsfor the accurate creation of dosage forms, which can help with drug product design. It also facilitates treatmentfor patients, such as individualized dosing, which can be used to treat particular disease states or patient groups.New approaches and techniques for creating unique medication delivery systems are made possible by theevolution of 3D techniques. The use of 3D printing technologies in the pharmaceutical industry is outlined inthis paper, with special consideration devoted to the benefits of these technologies for attaining quick medicationdelivery, personalized drug delivery, compound drug delivery, and customizable drug delivery. This articlealso demonstrates the history, advantages, prospects, applications, constraints, and difficulties of 3D printingtechniques in the area of developing pharmaceutical formulations. Pharmaceutical manufacturing is only one ofmany industries where the 3D printing (3DP) technique has had an important impact since its introduction in theearly 1980s. Researchers and the public are becoming more interested in creating customized or individualizeddosage forms as a result of the shifting horizons. The current work validates the viability of volumetric 3DP forquickly printing pharmaceutical items. This novel technology can enable the quick, on-demand manufacture ofpharmaceuticals and medical equipment with further optimization.